Characterization of three 1.5”x1.5”, 2”x2” and 3”x3” scintillators for the development of a chain for gamma spectroscopy - Villarreyes, Eduardo (2023)
Gamma radiation detectors using scintillators continue to be highly relevant in various fields such as the study of radiation in nuclear physics, in environmental radiation measurements, in radiological protection and in industry. The INFISA research group attached to the FCF of the UNMSM, which is located in the Physics Research Institute, has three inorganic solid scintillators of sodium iodide doped with thallium NaI(Tl) with a crystal size of 1.5”x1. 5” (REXON), 2”x2” (TELEDYNE) and 3”x3” (BICRON). In the present work we present the results of the comparison, showing the curves in both efficiency and resolution when characterizing the three scintillators for fine-tuning the detection chain for use in gamma spectroscopy.